International perspective - The, Sun (The Sun, 2016)
OWIN Jamasy Djamaludin, 54, hails from Sukabumi, West Java, Indonesia He enrolled in PhD (Arts) in Asia e University (AeU), Malaysia in January 2016. He works as a sociologist, community empowerment specialist, and researcher at the Ministry of Environment and Forestry, Indonesia.